Supplication and the Muslim personality: Psychological nature and functions of prayer as interpreted by Said Nursi - Tekke, Mustafa (Mental health, religion & culture, 2017)
Efforts to describe an Islamic psychology of religion must include the relationship that Muslims maintain with God through supplication. The Turkish theologian and scholar Said Nursi (1877-1960) offered useful theoretical guidance for understanding this issue. His perspective rested on the assumption that supplication finds its motivation in humanity’s innate shortcomings. Such imperfections encourage a person to communicate with God through supplication, and supplication then provides a source of felt closeness to God that defines how the Muslim personality should function. In broad terms, Nursi subdivided supplication into verbal (petitionary) and doing (behavioural) types. Verbal supplication helps persons respond to innate weaknesses by trusting in their own strengths, and this trust then manifests itself in the behavioural supplications that the individual uses to meet the demands of life. Nursi’s views suggest opportunities for empirically understanding supplication within an Islamic psychology of religion.